The Uniform grading tooL for flexIble ureterorenoscoPes (TULIP-tool): a Delphi consensus project on standardised evaluation of flexible ureterorenoscopes - ŞENER, TARIK EMRE (My University, 2022)
Objective To develop a standardised tool to evaluate flexible ureterorenoscopes (fURS). Materials and Methods A three-stage consensus building approach based on the modified Delphi technique was performed under guidance of a steering group. First, scope- and user-related parameters used to evaluate fURS were identified through a systematic scoping review. Then, the main categories and subcategories were defined, and the expert panel was selected. Finally, a two-step modified Delphi consensus project was conducted to firstly obtain consensus on the relevance and exact definition of each (sub)category necessary to evaluate fURS, and secondly on the evaluation method (setting, used tools and unit of outcome) of those (sub)categories. Consensus was reached at a predefined threshold of 80% high agreement. Results The panel consisted of 30 experts in the field of endourology. The first step of the modified Delphi consensus project consisted of two questionnaires with a response rate of 97% (n = 29) for both. Consensus was reached for the relevance and definition of six main categories and 12 subcategories. The second step consisted of three questionnaires (response rate of 90%, 97% and 100%, respectively). Consensus was reached on the method of measurement for all (sub)categories. Conclusion This modified Delphi consensus project reached consensus on a standardised grading tool for the evaluation of fURS - The Uniform grading tooL for flexIble ureterorenoscoPes (TULIP) tool. This is a first step in creating uniformity in this field of research to facilitate future comparison of outcomes of the functionality and handling of fURS.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Health Sciences; ÜROLOJİ VE NEFROLOJİ; Klinik Tıp; Klinik Tıp (MED); UROLOGY & NEPHROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Üroloji; Urology; flexible ureterorenoscope; quality assessment; evaluation; tool; endourology; Delphi consensus; EndoUrology; UroStone; Urology; IN-VITRO; URETEROSCOPES; lexible ureterorenoscope; quality assessment; evaluation; tool; endourology; Delphi consensus